A comparison on the working poor population in some European Countries - Bruder Emese (VADYBA, 2012)
The working poor population had not been gained any emphasis in Europe until the European Union adopted the Lisbon Strategy in 2000 with a special focus on employment, economy and social policies. In the framework of the Lisbon Strategy, the EU has started to develop a list of statistical indicators on poverty and social exclusion. These indicators aimed to control country level development on the agreed common goals, and they were adopted in 2001 at Laeken Council meeting in Belgium. In 2003, a new indicator, the in-work poverty risk has been added to the Laeken indicators. Since then, the existence of working poor population has took a more prominent place in the European debate. The objective of this paper is to give an insight of the situation of the working poor population in Visegrad countries, Czech Republic, Slovakia, Poland and Hungary and compare the results with the Benelux states. These groups of countries both have shared history, and common path in European integration. We analyze the extent of working poverty, the gender asymmetry and the full-time, part-time proportions over working poor population. Based on the 2007 wave of EU-SILC database, we individualize various income sources received by the household in order to obtain total individual incomes. With this approach, we would like to show how each individual would perform, if he/she could only rely on his/her own income. Keywords: poverty, working poor, inequality.